2019
DOI: 10.1016/j.soard.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal switch in revisional bariatric surgery: conclusions from an expert consensus panel

Abstract: Duodenal switch in revisional bariatric surgery. Duodenal switch in revisional bariatric surgery: conclusions from an expert consensus panel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Only 3.9% of surgeons would perform BPD/DS as second stage procedure for patients BMI greater than 50 kg/m 2 . Safety and efficacy of conversional surgeries have been confirmed by several studies [26,27,32,35,58,[61][62][63]. Moreover, as reported in previous published studies [27,32,35,61,63], there was a wide time interval between the two stages.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Only 3.9% of surgeons would perform BPD/DS as second stage procedure for patients BMI greater than 50 kg/m 2 . Safety and efficacy of conversional surgeries have been confirmed by several studies [26,27,32,35,58,[61][62][63]. Moreover, as reported in previous published studies [27,32,35,61,63], there was a wide time interval between the two stages.…”
Section: Discussionmentioning
confidence: 59%
“…The BPD/DS maybe the most effective bariatric procedure for patients with BMIs over 50 kg/m 2 as primary procedure [56,57] or as conversion after primary SG [58]. However, it may have higher rates of malnutrition, diarrhea and fecal incontinence [59].…”
Section: Discussionmentioning
confidence: 99%
“…Statistics in recent years have shown that the proportion of BPD/DS procedures among all bariatric and metabolic surgeries is gradually decreasing. At present, BPD/DS and related procedures are more often used in superobese (BMI ≥ 50 kg/m 2 ) patients or in those with inadequate weight loss after SG in the absence of reflux symptoms, with maximal %EWL ranging from 70% to 80% at two years [24] …”
Section: Bariatric Surgerymentioning
confidence: 99%
“…As a trial reports, 23 of 80 GERD patients receiving RYGB maintained reflux after 6 months, especially in patients with previous gastric banding. 104 With more postoperative complications, LTC should be avoided in LSG patients with GERD, BPD/DS, 105 , 106 and One-anastomosis gastric bypass (OAGB). 107 Manabu Amiki had the same conclusion, that is, LBPD/DS or duodenojejunal bypass (DJB) as revision surgery appears to be effective for further weight loss in the medium term, and laparoscopic RYGB appears to be effective for GERD remission.…”
Section: Revisional Surgeries For Complications Of Lsgmentioning
confidence: 99%